Developing a Comprehensive Public Policy Strategy for The Tourism Sector: Welcome to The Post-Covid-19 Pandemic - Nafis Dwi Kartiko (East Java Economic Journal, 2022)
This study analyzes the impact of the COVID-19 pandemic on the tourism sector. Policy research is chosen to formulate appropriate policies for the government. Quantitative and qualitative descriptive methods carried out the analysis. Descriptive analysis is used by looking at various existing policies and the impact of these policies on the tourism sector. At the same time, the quantitative method is used to see the determinant factors that affect the tourism sector. Qualitative methods allow researchers to explore several possibilities broadly in analyzing the subject matter. The data used is sourced from the Central Statistics Agency and the Ministry of Finance of the Republic of Indonesia. The researcher concludes that there should be adjustments to existing policies to support the acceleration of recovery in the tourism sector. The government can consider the determinants that affect the number of tourists to support the policies that will be formulated.